Functional foods, ageing and degenerative disease (Woodhead, 2004)
This book reviews the role of functional foods in helping to prevent a number of degenerative conditions, from osteoporosis and obesity to immune system disorders and cancer. The book begins with a discussion of the regulation of functional foods in the EU and the role of diet in the prevention of degenerative disease. Part 1 examines bone and oral health. Part 2 explores how obesity can be controlled and Part 3 looks at gut health and maintaining the immune function using functional ingredients such as probiotics and prebiotics. Part 4 reviews research on functional foods and cancer with chapters on synbiotics, anti-angiogenic functional foods, glucosinolatese, dietary fiber, and phytoestrogens.